Retorikang Filipino - 4 0 16; Bisa, Simplicio P.; 5 (Malate, Manila : De La Salle University Press, 1995)
Grammar of Tagalog language of the Philippines.
Includes bibliographical references (p. 137-138).
In Tagalog.
Keywords: 2 -- 0; 6; Grammar. -- Tagalog language -- 20; 20; 2